Chemical Composition of White Wines Produced from Different Grape Varieties and Wine Regions in Slovakia - Silvia Jakabová (MDPI AG, 2021)
In this work, chemical parameters such as sugar (glucose and fructose) content, organic acid (total acids, malic and tartaric acids), total phenolic content and the antioxidant activity of 12 white wines (chardonnay, pinot blanc and pinot gris) from various wine regions in Slovakia were studied in order to identify differences among the varieties and wine-growing regions. The wine samples were examined by Fourier-transform infrared spectroscopy (FTIR) and UV-VIS spectrophotometry (for determination of total polyphenolic content (TPC) and total antioxidant activity (TAA)) methods. Content of alcohol ranged between 11.50% and 13.80% with the mean value 12.52%. Mean content of total acids varied between 4.63 ± 0.09 and 6.63 ± 0.05 g.L−1, tartaric acid varied between 1.62 ± 0.09 and 2.93 ± 0.03 g L−1, malic acid was found in the concentrations ranged from 0.07 ± 0.05 and 2.50 ± 0.08 g L−1 and lactic acid was present between 1.53 and 0.01 g L−1. The content of fructose was, in general, higher in the samples from the Južnoslovenská and Nitrianska wine regions and glucose was higher in the Malokarpatská wine region. Chardonnay wines showed the highest content of total polyphenols and the antioxidant activity in the samples ranged from 51.06 ± 027 to 72.53 ± 0.35% inhibition of DPPH. The PCA analysis based on chemical descriptors distinguished the Nitrianska and Stredoslovenská wine regions. According to similarities among the wine samples, four main classes were formed by cluster analysis.